Development of nanoemulsion containing Parthenium hysterophorus L. crude extract for pre-emergence herbicide formulation - Zainuddin, Noorul Jannah (2019)
A nanoemulsion containing Parthenium hysterophorus crude extract (PHCE) was developed with the aim to introduced nanoemulsion as delivery system for PHCE in pre-emergence herbicide formulation. Parthenium hysterophorus is a noxious plant containing allelochemical parthenin with an ability to inhibit the growth of neighbouring plants. The study on herbicidal activity of P. hysterophorus was widely reported however, the study on development of PHCE in herbicide formulation was less explored. Nanoemulsion was proposed as the delivery system for PHCE to increase the efficiency and stability of plant crude extract. The use of natural-based active ingredients and adjuvants in nanoemulsion herbicide formulation was thought to be more environmental friendly compared to conventional synthetic herbicide. In the initial stage of the study, the local invasive weed known as Rumput Miang Mexico (RMM) was genetically identified as P. hysterophorus by using Internal Transcribes Spacer (ITS) region-based. The collected DNA sequence was registered in NCBI GenBank® under accession number of KY249559. The amount of the main allelochemical (parthenin) was determined to be 26.74 mg g-1 of dry plant by using UPLC-MS spectroscopy analysis. In the development of P. hysterophorus nanoemulsion (PHNE) formulation, several oil were tested to solubilize PHCE. Form the result, palm kernel oil ester (PKOE) was chosen as the oil phase due to the highest concentration of parthenin (2.43 ± 0.07 mg mL-1) was solubilized as compared to the other tested oils. Phase behaviour of P. hysterophorus crude extract (PHCE) was studied by construction of ternary phase diagrams using different surfactants. High solubilisation capacity (isotropic region) was obtained by mixture of surfactants Tensiofix and Tween 80 (ratio 8:2) compared to the other mixture of surfactants. One spot was selected as pre-formulation from the isotropic region of PKOE: PHCE (3:1)/ Tensiofix: Tween 80 (8:2)/ water system and further become the starting point for composition optimization of PHNE. Mixture Experimental Design (MED) modelling was used to determine the optimal composition of PHNE. From the optimization process, analysis of variance (ANOVA) showed a fit quadratic polynomial model for four independent variables (PKOE, Tensiofix: Tween 80 (8:2), PHCE and water) in relation to particle size. The model suggested an optimal formulation composition which contained 30.91 % of PKOE, 28.48 % of mixed surfactants (Tensiofix and Tween 80, 8:2), 28.32 % of water and 12.29 % of PHCE with the smallest particle size (140.10 nm) was obtained. The reading of both experimental and predicted particle size in the verification experiment was acceptable with a residual standard error (RSE) less than 2 %. Under the optimal condition, the particle of final formulation was clearly shown by morphology analysis to be spherical in shape and demonstrated an average particle size which is in agreement with dynamic light scattering analysis. The optimized nanoemulsion demonstrated a good stability (no phase separation) under centrifugation and different storage conditions (25 ± 5 °C and 45 °C). Manipulating time as parameter, nanoemulsion stored for 60 days exhibit monodisperse emulsion with narrow distribution of polydispersity index values (0.07 to 0.08), stable zeta potential values (± 25 mV) and slight increase of particle size (143.0 nm to 218.5 nm). The increase in particle size over time might have been contributed by Oswald ripening phenomenon which was shown by a linear graph from Oswald ripening rate analysis. In the efficiency test, PHNE was compared with PHCE in terms of surface tension and phytotoxicity against Diodia ocimifolia seed. PHNE displayed lower surface tension in comparison to PHCE which suggested that nanoemulsion might have enhanced the ability of the plant crude extract to penetrate through plant seed coat. In addition, PHNE was shown to cause total inhibition of D. ocimifolia seed at lower concentration (5 g L-1) than PHCE (10 g L-1). The ability of PHCE to inhibit D. ocimifolia seed was almost doubled after being formulated in nanoemulsion system by having half effective dose (ED50) value for PHNE (1.93 g L-1) and PHCE (3.60 g L-1). Similarly to the seed germination, PHNE shown to be more efficient in reducing the growth of radicle and shoots of D. ocimifolia in compared to the plant crude extract. The finding of the research could potentially serve as a platform for development of a natural herbicide formulation from crude plant extract for green weed management.